Characteristics of Patients Returning to Work After Brain Tumor Surgery - Schiavolin, Silvia; Mariniello, Arianna; Broggi, Morgan; Acerbi, Francesco; Schiariti, Marco; Franzini, Angelo; Di Meco, Francesco; Ferroli, Paolo; Leonardi, Matilde (Frontiers in Human Neuroscience, 2021)
Objective: To investigate the differences between patients returning to work and those who did not after brain tumor surgery. Methods: Patients were evaluated before surgery and after 3 months. The Montreal Cognitive Assessment test, Trail-Making Test (parts A and B), 15-word Rey–Osterrieth Word List (immediate and delayed recall), F-A-S tests, and Karnosfky Performance Status were used to assess cognitive status, attention, executive functions, memory, word fluency, and functional status. Patient-reported outcome measures (PROMs) used to evaluate emotional distress and disability were the Hospital Anxiety and Depression Scale and World Health Organization Disability Assessment Schedule. Clinical and work-related variables, PROMs, and cognitive tests were compared using chi-squared, t-test or Mann–Whitney U test. Results: Sixty patients were included. Patients returning to work were 61.3 and 31.0% among people with meningioma and glioma, respectively. They reported lower postoperative disability and lesser home-to-work travel time. Patients with meningioma also showed better preoperative and postoperative attention and executive functions, better postoperative functional and cognitive status, and lower frequency of treatments. Conclusions: These variables should be considered in a clinical context to plan interventions for people who need support during return to work and in future research to investigate preoperative and postoperative predictive factors of going back to work.